2004
DOI: 10.1007/s00520-004-0673-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a scheme to enhance palliative cancer care in rural Wales

Abstract: Since the early 1990s, the United Kingdom has seen several initiatives designed to improve the quality of cancer palliative care in the community. We report on the evaluation of a project that took place in the rural county of Powys in Wales in which a group of general practitioner clinical facilitators (GPCFs) sought to raise the overall standard of palliative care among primary health care teams (PHCTs). The evaluation was conducted over 3 years and made use of several methods: interviews with facilitators a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…One intervention showed that the reference patterns to specialists made by the GP did not change, although the mean number of patients visited by specialists decreased significantly after the intervention. 25 In another study, the utility perception of PC services was significant. 41 Knowledge, attitude, satisfaction of physicians.…”
Section: Measures Of Change In the Learning Culture Of Physiciansmentioning
confidence: 95%
See 3 more Smart Citations
“…One intervention showed that the reference patterns to specialists made by the GP did not change, although the mean number of patients visited by specialists decreased significantly after the intervention. 25 In another study, the utility perception of PC services was significant. 41 Knowledge, attitude, satisfaction of physicians.…”
Section: Measures Of Change In the Learning Culture Of Physiciansmentioning
confidence: 95%
“…Outcomes registered (a) Related to the professional: objective measures of symptom control. The analysis of opioid prescription in two interventions showed a partial improvement in the increased use of morphine in one study, 25 and decreased use of fentanyl patches in both studies. 25,30 However, prescription of morphine solution was unchanged in one intervention, 30 a clear discrepancy to the answers of the questionnaires previously administered in the study.…”
Section: Quality Of Included Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…These findings are reflected in the international arena. 10 A study conducted in Spain by Porta et al 11 explored urban, suburban, and rural GPs' assessments of support provided to the families of patients with terminal cancer. It was found that, the more rural the environment in which GPs worked, the more likely they were to acknowledge the need for providing ongoing support for patients and families.…”
Section: The Role Of the Rural Gp In Palliative Carementioning
confidence: 99%